Effect and mechanism of microRNA-10b on proliferation and invasion of esophageal cancer cells - Liu, Yi (Exp Ther Med, 2019)
MicroRNA (miR)-10b is highly expressed in esophageal cancer tissues and is associated with poor prognosis of esophageal cancer. However, the role and mechanism of miR-10b in esophageal cancer cells remains unclear, therefore, the present study aimed to investigate this. Esophageal cancer cells, TE-1 and EC9706, were transfected with miR-10b mimic, miR-10b inhibitor or incubated with transforming growth factor-β (TGF-β). MTT and EdU assays were used to detect cell proliferation. Flow cytometry was used to determine cell cycle analysis and apoptosis. Cell migration and invasion were also analyzed. Western blot analysis was used to detect protein levels and reverse transcription-quantitative PCR was used to analyze miR-10b expression. The present results demonstrated that, compared with the control group, miR-10b significantly promoted TE-1 and EC9706 cell proliferation. Compared with miR-10b inhibitor group and control group, miR-10b mimic promoted esophageal cancer cell cycle progression, inhibited apoptosis of esophageal cancer cells and promoted the migration and invasion of cells. The proliferation of esophageal cancer cells increased in a dose-dependent manner with TGF-β concentration. TGF-β treatment induced high expression of miR-10b in both cell lines. The miR-10b mimic + TGF-β group further promoted the migration and invasion of esophageal cancer cells. Western blot analysis determined that, compared with the control group, miR-10b mimic increased TGF-β expression. miR-10b mimic also inhibited the expression of phosphatase and tensin homolog (PTEN) in tumor cells. Compared with the control group, TGF-β inhibited the expression of PTEN with the miR-10b mimic + TGF-β group further inhibiting the PTEN. miR-10b inhibitor + TGF-β reversed the effect of TGF-β and miR-10b on PTEN. In conclusion, miR-10b promoted cell cycle progression, inhibited apoptosis and promoted the migration and invasion of esophageal cancer cells. The mechanism may be related to the upregulation of TGF-β and the downregulation of PTEN. The present findings suggested that miR-10b might be a potential therapeutic target for esophageal cancer.